EphrinB2/EphB4 Signaling Regulates DPSCs to Induce Sprouting Angiogenesis of Endothelial Cells. (July 2019) - Gong, T.; Xu, J.; Heng, B.; Qiu, S.; Yi, B.; Han, Y.; Lo, E.C.M.; Zhang, C.
Dental pulp stem cells (DPSCs) are capable of facilitating angiogenesis resembling pericytes when located adjacent to endothelial cells (ECs). Nevertheless, the precise mechanisms orchestrating their proangiogenic functions remain unclear. Using a 3-dimensional (3-D) fibrin gel model, we aimed to investigate whether EphrinB2/EphB4 signaling in DPSCs plays a role in supporting vascular morphogenesis mediated by ECs, together with the underlying mechanism involved. The EphrinB2/EphB4 signaling was inhibited either by a pharmacological inhibitor of EphB4 receptor or by knocking down the expressions of EphrinB2 and EphB4 using lentiviral small hairpin RNA (shRNA). DPSCs were either encapsulated in fibrin gel together with human umbilical vein endothelial cells (HUVECs) or cultured as a monolayer on top of HUVECs to investigate both paracrine and juxtacrine interactions simultaneously. Following 10 d of direct coculture, we found that pharmacological inhibition of EphrinB2/EphB4 signaling severely impaired vessel formation and laminin deposition. When directly cocultured with HUVECs, knockdown of EphrinB2 or EphB4 in DPSCs significantly inhibited endothelial sprouting, resulting in less capillary sprouts with reduced vessel length ( P < 0.05). By contrast, when DPSCs were not in direct contact with HUVECs, attenuation of EphrinB2 or EphB4 expression levels in DPSCs did not exert any significant effects on capillary morphogenesis. Noticeably, exogenous stimulation with soluble EphrinB2-Fc or EphB4-Fc (1 µg/mL) enhanced vascular endothelial growth factor (VEGF) secretion from DPSCs, thereby moderately promoting angiogenic cascades in the fibrin matrix. This study, for the first time, reveals a crucial role of EphrinB2/EphB4 signaling in regulating the capacity of DPSCs to induce sprouting angiogenesis. These findings advance our understanding of postnatal angiogenesis and may have future regenerative medicine applications.